Mind-Body-Spiritual Nursing Care Effects on Spirituality and Cardiovascular Risk Markers - Kurniawati, Ninuk Dian; Nursalam, Nursalam (International Journal of Psychosocial Rehabilitation, 2020)
Patients with coronary heart disease (CHD) undergoing hospitalization experience various stressors. These stressors may increase expression of cardiovascular risk marker molecules, resulting in building up atherosclerotic plaque. This study aimed at explaining the influence of a mind-body-spiritual nursing care on spirituality and cardiovascular risk markers. This study employed a pre-post-test quasi-experiment with control group design. CHD patients treated in various rooms divided into the control group (20 respondents) and the treatment group (21 respondents). The variables of interest were measured at both pre and post intervention. The spirituality was measured using a questionnaire, while the cardiovascular risk markers were tested using enzyme-linked immunoabsorbant assay from the respondents’ serum of venous blood sample. The control group received a standard-nursing intervention while the treatment group received a mind-body-spiritual (MBS) nursing care for three respective days. Data collection took place in 2017. The results showed that mind-body-spiritual nursing care improves patients’ spirituality (p = 0.000) and the cardiovascular risk markers, particularly VCAM-1 and MCP-1, but not the Hsp70 and eNOS. Additionally, pathway analysis shows that mind-body-spiritual nursing care firstly increases the CHD patients’ spirituality, which, in turn, attenuates the expression of VCAM-1 and MCP-1 through the improvement of Hsp70 expression. These findings indicate the mind-body-spiritual care’s potential in preventing the process of further build-up of atherosclerotic plaque in CHD patients. It can be concluded that MBS nursing care plays an important role in improving spirituality and thus the expression of cardiovascular risk markers.